Search for charginos nearly mass-degenerate with the lightest neutralino : based on a disappearing-track signature in pp collisions at √s = 8 TeV /: based on a disappearing-track signature in pp collisions at √s = 8 TeV. ([2016]) - Kazama, Shingo
No abstract available